2009
DOI: 10.1021/jf903388a
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Kinetics of 5-o-Caffeoylquinic Acid in Superheated Steam: Effect of Isomerization on Mate (Ilex paraguariensis) Manufacturing

Abstract: A set of experiments was carried out to investigate the chemical stability of 5-o-caffeoylquinic acid (5-CQA) in the presence of superheated steam. A batch cylindrical reactor made of glass and isothermally operated between 398 and 499 K was used in the experiments. A high-performance liquid chromatograph equipped with a diode array detector was applied to monitor the 5-CQA concentrations. The conversions of 5-CQA were correctly reproduced with a simplified kinetic model represented by a reversible pseudofirst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
4
15
0
Order By: Relevance
“…At approximately this wavelength, 5-CQA was proved to present maximum absorbance [6,7,9,11,21,26,29]. Available HPLC analyses of 5-CQA submitted to conditions of oxidation almost identical to those adopted in the current investigation [7] support the reliability of the current kinetic results based on absorbance measurements.…”
Section: Methodssupporting
confidence: 75%
See 2 more Smart Citations
“…At approximately this wavelength, 5-CQA was proved to present maximum absorbance [6,7,9,11,21,26,29]. Available HPLC analyses of 5-CQA submitted to conditions of oxidation almost identical to those adopted in the current investigation [7] support the reliability of the current kinetic results based on absorbance measurements.…”
Section: Methodssupporting
confidence: 75%
“…Although the role of these components (ubiquitous in fruits, vegetables and herbs) in the protective mechanism at cellular level has been extensively studied [2], the impact of typical food processing operations at high temperature (such as drying, enzymatic deactivation, roasting) on the chemical antioxidant nature of these species has been a matter of minor interest [6][7][8][9]. However, the rate of oxidation of CGA during food manufacturing in the presence of air is of great importance because the oxygen drastically contributes to reduce the content of these species [9][10][11][12][13] naturally found in the food, and eventually the beneficial impact of their intake on human health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dicaffeoylquinic acids (chlorogenic acids) and flavonoids showed the strongest effect (Zanoelo and Beninca, 2009). Along the same lines, a recent study in an animal model has shown that maté tea reduced acute lung inflammation in mice exposed to cigarette smoke.…”
Section: Effects Of Ilex Paraguariensis Extracts On Inflammationmentioning
confidence: 99%
“…As many other simple (chlorogenic, benzoic, cinnamic and coumaric acids) and polyphenol compounds (resveratrol, morin, quercetin) [5,6,[10][11][12], catechins (CATs) are antioxidants naturally found in plants, foods and drinks prepared from them [6,13,14]. CATs are also believed to present a protective role against cancer, viral infections and coronary diseases in humans that make them specially attractive for the food industry [6,15,13,14,16].…”
mentioning
confidence: 99%